Family Dynamics And The Psychosocial Well-Being Of Adolescents: A Cross Sectional Study (The Review of Diabetic Studies, 2024)
Background: Family dynamics play a pivotal role in shaping the psycho-social well-being of adolescents, particularly in Saudi Arabia (KSA), where cultural, social, and religious factors intertwine to influence the way families interact and raise their children. Significant emotional, cognitive, and social development characterize the adolescent years, and a young person's family environment greatly influences how they navigate these changes.The aim of the study: To assess family dynamics and the psycho-social well-being of in-school adolescents, with a view to determining the association between family dynamics and the psycho-social well-being of in-school adolescents. This provided a basis for planning family-oriented support services to improve the psycho-social health status of in-school adolescents.Study design: A descriptive cross-sectional design.Methods: Three hundred and thirty-five school-adolescents from public and private secondary schools in KSA were selected using the proportionate systematic random sampling technique. Data was collected with the Family Assessment Device questionnaire and Youth self-reported Pediatric Symptom Checklist and analyzed using descriptive and inferential statistics.Results: Findings showed that 53.7% of the participants had unhealthy family dynamics while 16.0% had impaired psycho-social status. There is a significant negative association between family dynamics in problem solving dimension and psychosocial health status with a Beta coefficient (-1.120), Odd ratio=0.326 (95% CI 0.171 to 0.624).Conclusion: Majority of in-school adolescents had unhealthy family functioning pattern and one in six adolescents had impaired psychosocial health. There was a negative but significant association between the problem-solving dimension of family dynamics and psycho-social health. Community health professionals should carryout preventive interventions among parents and adolescents in the community with adequate attention to all the dimensions of family functioning.